ChemInform Abstract: Enantioselective Synthesis of Hemiaminals via Pd‐Catalyzed C—N Coupling with Chiral Bisphosphine Mono‐Oxides. Issue 17 (April 2016) - Li, Hongming; Belyk, Kevin M.; Yin, Jingjun; Chen, Qinghao; Hyde, Alan; Ji, Yining; Oliver, Steven; Tudge, Matthew T.; Campeau, Louis‐Charles; Campos, Kevin R.
Abstract: A novel approach to the enantioselective synthesis of hemiaminals via Pd‐catalyzed C—N coupling using commercially available chiral bisphosphine ligands is developed.